ANALISIS PERBANDINGAN KINERJA KEUANGAN, ABNORMAL RETURN DAN VOLUME PERDAGANGAN SAHAM ANTARA PERIODE SEBELUM DAN SESUDAH MERAIH INDONESIA SUSTAINABILITY REPORTING AWARD (ISRA) - Teuku Muhammad Mauli Randina; Fachrizal Fachrizal (Accounting Departement Economics and Business Faculty Syiah Kuala University, 2016)
The objective of this study is to analyze the differences of financial performance, abnormal return and stock trade volume in companies who have achieved ISRA in 2012-2014 period. This event study observed the financial performance with net profit margin, sales growth and earnings per share as its proxies at the time of 3 years before and 3 years after the achievement of ISRA. This study also observed the abnormal return and stock trade volume at the time of 5 days before and 5 days after the event. This study used secondary data; financial reports, closing stock prices and daily stock trade volume from Bursa Efek Indonesia. Samples used in this study were the companies that achieved ISRA award in 2012-2014 period.The result showed that: (1) There was no significant differences in financial performance between the period prior to ISRA achievement and the period after the achievement when the proxies used were net profit margin and sales growth. But with earnings per share used as financial performance proxy, The differences between periods were exist. (2) There was no significant difference in abnormal return between the period prior to ISRA achievement and the period after the achievement. (3) There were significant differences in stock trade volume between the period prior to ISRA achievement and the period after the achievement. Keywords - net profit margin, sales growth,earnings per share, abnormal return, stock trade volume, ISRA.